Sintering behaviour of hydroxyapatite prepared from different routes - S., Ramesh; C.Y., Tan; Ranna, Tolouei; M., Amiriyan; J. , Purbolaksono; Iis, Sopyan; W.D., Teng (Elsevier, 2012)
The sintering behavior of three different types of hydroxyapatite (HA) i.e. a commercial powder, HA(C), a synthesized powder by wet chemical precipitation method, HA(W) and a synthesized powder by mechanochemical method, HA(M) were investigated over the temperature range of 1000–1350 °C. It has been revealed that the sinterability and mechanical properties of the synthesized HA(W) was significantly higher than that of the HA(C) and HA(M). The optimum sintering temperature for the HA(W) samples was 1100 °C with the following properties being recorded: 99.8% relative density, Vickers hardness of 7.04 GPa and fracture toughness of 1.22 MPa m1/2. In contrast, the optimum sintering temperature for the HA(C) and HA(M) samples was 1300 °C with relative density of 98% and 95.5%, Vickers hardness of 5.47 GPa and 4.73 GPa, fracture toughness of 0.75 MPa m1/2 and 0.82 MPa m1/2 being measured. The present research showed that the wet chemical precipitation reaction was beneficial in producing a highly crystalline, high purity and single phase stoichiometric HA powder that is sinteractive particularly at low temperatures below 1100 °C.